Host Cell Copper Transporters CTR1 and ATP7A are important for Influenza A virus replication. Issue 1 (December 2017) - Rupp, Jonathan; Locatelli, Manon; Grieser, Alexis; Ramos, Andrea; Campbell, Patricia; Yi, Hong; Steel, John; Burkhead, Jason; Bortz, Eric
Abstract Background The essential role of copper in eukaryotic cellular physiology is known, but has not been recognized as important in the context of influenza A virus infection. In this study, we investigated the effect of cellular copper on influenza A virus replication. Methods Influenza A/WSN/33 (H1N1) virus growth and macromolecule syntheses were assessed in cultured human lung cells (A549) where the copper concentration of the growth medium was modified, or expression of host genes involved in copper homeostasis was targeted by RNA interference. Results Exogenously increasing copper concentration, or chelating copper, resulted in moderate defects in viral growth. Nucleoprotein (NP) localization, neuraminidase activity assays and transmission electron microscopy did not reveal significant defects in virion assembly, morphology or release under these conditions. However, RNAi knockdown of the high-affinity copper importer CTR1 resulted in significant viral growth defects (7.3-fold reduced titer at 24 hours post-infection, p = 0.04). Knockdown of CTR1 or thetrans -Golgi copper transporter ATP7A significantly reduced polymerase activity in a minigenome assay. Both copper transporters were required for authentic viral RNA synthesis and NP and matrix (M1) protein accumulation in the infected cell. Conclusions These results demonstrate that intracellular copper regulates the influenza virus life cycle, with potentially distinct mechanisms in specific cellular compartments. These observations provide a new avenue for drug development and studies of influenza virus pathogenesis.